2001
DOI: 10.1046/j.1365-2648.2001.01818.x
|View full text |Cite
|
Sign up to set email alerts
|

The concept of care in male nurse work: an ontological hermeneutic study in acute hospitals

Abstract: The reflections of these participants emphasize the emotional load of practice and a sensitivity on their part to the male stereotype of being able to cope with such pressures. It is suggested therefore that those providing and managing clinical supervision take into account the possible reluctance of male nurses to seek such support. Issues of gender should be emphasized in nurse education, as these nurses were sensitive to the impact of gender on their practice, both with patient/clients and their significan… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
35
2
1

Year Published

2004
2004
2023
2023

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 44 publications
(39 citation statements)
references
References 23 publications
1
35
2
1
Order By: Relevance
“…The gender barrier faced by male nurses has been discussed in previous studies (Keogh & Gleeson, 2006;Lodge et al, 1997). A chaperone and a sense of humor could improve nurse-patient relationships (Milligan, 2001). Our study also explored the chaperone issue.…”
Section: Discussionmentioning
confidence: 91%
“…The gender barrier faced by male nurses has been discussed in previous studies (Keogh & Gleeson, 2006;Lodge et al, 1997). A chaperone and a sense of humor could improve nurse-patient relationships (Milligan, 2001). Our study also explored the chaperone issue.…”
Section: Discussionmentioning
confidence: 91%
“…They encounter unequal treatment in the workplace (7,8) and prejudice from patients and society (9). They report feeling ashamed (8) and embarrassed when providing personal care to female patients (10).…”
Section: Data Collectionmentioning
confidence: 99%
“…More recently, Milligan (2001) examined the concept of care in relation to the experience of eight men nurses in Britain. Once again, the importance of gender was identified in relation to the association of men with physical strength as Milligan reported that men nurses were called upon to do the manual handling and the heavy physical work of patient care.…”
Section: Review Of the Literaturementioning
confidence: 99%
“…Dominant cultural definitions of masculinity and mens bodies shape men nurses everyday work and the roles they expect and are expected to assume. As such, mens bodies and notions of masculinity impact men nurses relationships with women patients and women colleagues, their career opportunities, and ultimately, their overall satisfaction and success with nursing as a career (Heikes, 1991;McClain, 1999;Milligan, 2001;Whittock & Leonard, 2003). Using the voices of men nurses themselves, the experience of eight men registered nurses in Nova Scotia, Canada reveals how mens bodies and meanings of masculinity structure a gendered division of labor which reflects and reinforces patriarchal gender relations and stereotypical beliefs about men and masculinity (Bush, 1976;Heikes, 1991;Kelly, Shoemaker & Steele, 1996).…”
mentioning
confidence: 99%